The Meaning Of Entrepreneurship Learning For Students In Higher Education - Setiawan, Rahyuniati; Mubarok, Teten Mohamad Sapril; Maulani, Galih Abdul Fatah; Rahmawati, Putri; Adiansyah, Adi (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
The absorption of the meaning of entrepreneurship education in students is not yet fully optimal. It is identified that the absorption capacity of jobs generated by MSMEs is very high and makes MSMEs the mainstay of the economy in Indonesia. The purpose of this research is to provide meaning regarding entrepreneurship learning for students in higher education. The research method used is a qualitative descriptive study using observation, interview and documentation study techniques, through data reduction analysis, data presentation, data verification and data conclusions. The results of the study show that students feel more motivated to start their own businesses after taking entrepreneurship education. Entrepreneurship education not only functions as a guideline for entrepreneurship, but also as an important tool in creating solutions to economic problems faced by society. Therefore, entrepreneurship learning provides a good meaning in supporting student performance in the future.